Hybrid finite element-boundary element method for nonlinear electromagnetic problems - Trlep, M.; Skerget, L.; Kreca, B.; Hribernik, B. (IEEE transactions on magnetics, 1995)
The paper deals with the application of the hybrid finite element-boundary element method in the computation of linear and nonlinear magnetostatic field with a vector potential for 2D and with a scalar potential for 3D problems. The nonlinear part of the domain is solved by finite elements, while in the linear part of the domain, the boundary elements are used. Different boundary formulations are developed to overcome the coupling problems. "Mixed" boundary elements are coupled with linear finite elements, for both 2D and 3D problems. Typical examples are presented: electrical motor and the IEEJ model.< >